Integrating Servant Leadership and Coaching: Toward Transformative Educational Leadership in A Faith-Based School Board in Surabaya - Ricky (Aletheia Christian Educators Journal, 2025)
This study explores how servant leadership is enacted through coaching within a Christian school board in Surabaya. While servant leadership is widely upheld in faith-based education, its integration with coaching remains underexamined. This research addresses three questions: (1) how school leaders understand coaching as part of servant leadership, (2) how they practice it, and (3) what enables its implementation. Employing a qualitative approach, data were collected through interviews with ten school leaders and analyzed using Miles, Huberman, and Saldaña’s (2014) framework. Findings reveal that servant leadership coaching (SLC) is shaped by leaders’ inner convictions, especially their sense of divine calling and belief that leading means helping. SLC emerges as a holistic practice encompassing spiritual formation, personal care, and professional development. However, effective implementation depends on two enabling factors: (1) training that builds coaching competence and trustworthiness, and (2) school policies that institutionalize SLC formally while also allowing it to flourish organically. These findings expand existing SLC models by emphasizing vocational identity, relational integrity, and organizational culture as key elements. This study offers a faith-integrated servant leadership coaching in Christian schools, positioning coaching as an effective servant leadership enactment.